Maturogenesis of non-vital immature permanent teeth - Ritesh R Kalaskar; Ashita R Kalaskar (Wolters Kluwer Medknow Publications, 2013)
Pulpal necrosis in young permanent teeth often results in teeth with open apex, thin root walls and poor crown root ratio. Out of the available treatment options maturogenesis has been the most conservative option that exploits full potential of pulp for dentin deposition. Maturogenesis involves disinfecting the root canal system followed by stimulation of blood clot from the periapical tissue, which provides a matrix into which the cell could grow and sealing the coronal excess. In the present case report, tri antibacterial paste (3 Mix) was used as an intracanal medicament that proved successful in stimulating vital pulp cells of the periapical region for maturogenesis. Five months radiograph follow-up showed thickening of lateral dentinal walls, which progress until 15 months resulting in apical closure, thickening of lateral dentinal walls and increase root length.